Enhanced Honey Bees Colony Algorithms For Protein Tertiary Structure Prediction - Bahamish, Hesham Awadh Abdallah (2011)
There is no doubt about the role that protein plays in the biological processes inside the human body. Proteins are able to perform their biological functions when they fold into their tertiary structure. Experimental protein tertiary structure prediction methods are time consuming and expensive and it is not always possible to determine the protein structure experimentally. Scientists from many fields work to develop theoretical and computational methods which provide cost effective solutions to the protein structure prediction problem.